THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND STRESS LEVELS WITH THE MENSTRUAL CYCLE IN ADOLESCENTS - Fitriani; Yesita Ragil K; Febriana Tri Kusumawati; Jayanti Dwi Puspitasari (The Shine Cahaya Dunia D-III Keperawatan, 2026)
Background: Menstrual cycles should occur every month with intervals of 21-35 days for each cycle. Irregularities in the menstrual cycle can indicate problems with the hormonal and metabolic systems. Several factors influence this cycle variation, including stress. Stress levels and nutritional status also play a role in disrupting the menstrual cycle. Methods: This study employed a descriptive correlational approach with a cross-sectional design. The sample used in this study consisted of 88 individuals, divided into 44 subjects for nutritional status analysis and 44 subjects for stress levels. Data processing was performed automatically using SPSS software, performing univariate and bivariate analyses, and the statistical test used was the Chi-square test. Results: The univariate analysis showed that 60% of respondents experienced mild stress and 67.4% exhibited an irregular menstrual cycle. The univariate analysis also showed that 60% of respondents suffered from malnutrition and 67.4% experienced an abnormal menstrual cycle. The first bivariate analysis showed a p-value of 0.000, indicating a relationship between stress levels and menstrual cycles. The second bivariate analysis showed a p-value of 0.000, indicating a relationship between nutritional status and menstrual cycles. Conclusion: This study concluded that there is a relationship between nutritional status and stress levels and menstrual cycles in female students, with a p-value of 0.001.